The association of adiponectin gene expression and serum levels with susceptibility to peripheral polyneuropathy in Egyptian patients by women with hypothyroidism - Nearmeen M Rashad; Mohamed S.S Saad; Bothina M Ramadan; Shereen M El Shabrawy (SpringerOpen, 2019)
Background Hypothyroidism has numerous comorbidities including degenerative neurological disease and insulin resistance. Adiponectin is an adipokine secreted by adipose tissue with insulin-sensitizing, anti-inflammatory, and antioxidant properties. This study was designed to explore the expression pattern of Adiponectin and its serum level in hypothyroidism and peripheral neuropathy (PN). The aim was to also evaluate the association between the expression pattern of adiponectin and its serum level with the clinical and electrophysiological tests of PN in hypothyroid patients. Participants and methods This cross-sectional controlled study enrolled 110 hypothyroid patients and 80 control group participants. All participants were subjected to a complete neurological examination and nerve conduction study (NCS). Adiponectin level was measured using an enzyme-linked immunosorbent assay. Adiponectin expression levels were estimated using real-time PCR. Results The results showed lower values of serum adiponectin and adiponectin expression levels in hypothyroid patients, especially patients with PN. NCS in the studied group showed that motor and sensory nerve conduction in the median and posterior tibial nerves were significantly decreased in both hypothyroid patients with or without PN compared with the euthyroid group. In addition, serum adiponectin and adiponectin expression were negatively correlated with Toronto Clinical Scoring System as well as cardiometabolic risks and positively correlated with NCS of the median, sural, and tibial nerves. The diagnostic power of adiponectin expression is better than that of adiponectin serum levels. Conclusion Hypothyroid patients with PN had lower values of serum adiponectin and adiponectin expression levels than hypothyroid patients without PN; the diagnostic power of combined adiponectin serum and expression levels was thus highly significant, and they could be a useful diagnostic biomarker of PN.